Peran Mahasiswa PGMI dalam Peningkatan kemampuan mengenal angka dalam Bahasa Inggris melalui media papan angka di MIN 3 Kota Palangka Raya - Widiya; Zaitun Qamariah; Nur Inayah Syar (Fakultas Ekonomi dan Bisnis Unversitas Islam Raden Rahmat, 2024)
This study aims to explore the role of Madrasah Ibtidaiyah Teacher Education (PGMI) students in enhancing the ability of MIN 3 Kota Palangkaraya students to recognize numbers in English through the use of number board media. The method used is classroom action research involving PGMI students as facilitators and mentors. The results show that the use of number board media significantly improves students' understanding and ability to recognize and pronounce numbers in English. The interactive and innovative learning process through this media also increases students' interest and motivation in learning. The guidance provided by PGMI students positively impacts the quality of learning, creating a more enjoyable and conducive learning environment. In conclusion, the active role of PGMI students in implementing creative learning media such as the number board is very effective in improving students' English language skills.